Characterization of granitic subsurface profile by borehole logging and seismic refraction method - Ahmadol, Afifi Fahmi (2020)
Due to tropical climate in nature of Malaysia, related region experience extreme weathering process that lead to unique subsurface profile. As weathering process proceed from the surface down and inwards, from joint surfaces and other percolation paths, the intensity of the weathering generally reduces as depth increases. The seismic refraction method had been used to determine the rock characteristic of the study area. This study aim to characterize the granitic area by seismic refraction method and boreholes information at Sungai Long Quarry, Cheras. This study involve 6 lines of seismic refraction and 6 boreholes that were drilled on the same paths. The study was conducted by using the ABEM MK-8 (seismograph), a 6.5kg sledgehammer with a steel plate and 24 channels geophones. EasyRefract software been used to process the seismic refraction survey data, which based on primary waves velocities distributed from seismograph. Results obtained from the conventional borehole logging, which are the N-value Standard Penetration Test, Core Recovery Ratio and Rock Quality Designation, were evaluated and correlated with primary wave velocity for subsurface interpretation. Results were found that the correlation between Core Rock Recovery give better correlation with seismic velocity value as compared to Rock Quality Designation. Correlation of both ground investigation exhibit an indicator for producing N-values prediction especially in a tropical granitic setting environment. N-values 50 of each boreholes recorded between 1140m/s to 1513m/s whereas N-values below 50 were recorded less than 800m/s. In addition, the highly weathered zone interpreted in the survey lines could be related to the medium dense to dense material that exist on top of boulder. On the other hand, N-value shows fair correlation to seismic velocity which exhibit value less than 1500m/s. Generally, both RQD of 0% to 97% and CRR of 33% to 100% values shows seismic velocity values, which ranges from 750 m/s to 2100m/s. The wide range of value is due to thick soil profile before reaching the bedrock. Hence, some masking affect contributed to the variation of depth.